Effect of temperature regimes on seed germination asafoetida (Ferula assafoetida L.) - Zangoie, M.; Parsa, S.; Mahmoodi, M.; Al-Ahmadi, M. Jami; Sanjari, G. (Plant Breeding and Seed Science, 2014)
Asafoetida is a medicinal plant belonging to the Apiaceae family. Gum obtained from the lower part of the stem and roots of this plant has many industrial and pharmaceutical applications. This plant is subject to extinction in its natural habitats due to over-utilization. Understanding the biology of seed germination can help to restore such degradation by implementing agricultural development programs. The present study is an attempt to determine the germination responses to two temperature regimes (constant and fluctuating) during the course of the study. The experiment was planned based on a factorial-completely randomized design with two factors (constant and fluctuating temperature regimes) at 3 levels each (15, 20 and 25°C) with 4 replications. The results showed that the characteristics of germination in asafoetida were significantly improved under the fluctuating temperature as compared with the constant regime. It showed a mean germination time of 1.88 days for the fluctuating regime, while it was 4.88 days for the constant regime. The same results were found on germination rates in favor of fluctuating (0.62 per day) in comparison with constant regime (0.33 per day). Under the fluctuating regime, the lowest level of imposed temperature (daily application of 10 and 20 degree during the first and the second 12 hours, respectively) was the best for seed germination in this experiment.